1994
DOI: 10.1021/ac00079a005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of the Factors Affecting Nonionic Surfactant-Mediated Phase Separations

Abstract: The technique of extracting and concentrating hydrophobic species from water via nonionic surfactant micelle-mediated phase separations was examined. The effect on extraction efficiency, solute distribution coefficient, and phase volume ratio of pertinent experimental parameters such as surfactant hydrophobicity, pH and ionic strength, equilibration time and temperature, centrifuge time, and analyte and surfactant concentration was systematically evaluated. Surfactant hydrophobicity, which was studied by monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
132
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(134 citation statements)
references
References 31 publications
0
132
1
1
Order By: Relevance
“…In order to employ the lowest possible equilibration temperature to the efficient separation of phases, the equilibration temperature was examined. Theoretically, the optimal equilibration temperature of the extraction occurs when the equilibration temperature is 15-20 • C greater than the cloud point temperature of surfactant [26]. Fig.…”
Section: Effect Of the Equilibration Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to employ the lowest possible equilibration temperature to the efficient separation of phases, the equilibration temperature was examined. Theoretically, the optimal equilibration temperature of the extraction occurs when the equilibration temperature is 15-20 • C greater than the cloud point temperature of surfactant [26]. Fig.…”
Section: Effect Of the Equilibration Temperaturementioning
confidence: 99%
“…When the cloud point extraction procedure was processed at equilibration temperature of the surfactant, the best extraction effect was achieved [26]. Thus, it is necessary to examine the effect of temperature on cloud point extraction.…”
Section: Effect Of the Equilibration Temperaturementioning
confidence: 99%
“…This ratio increases with a decrease in the concentration of the surfactant. 29 However, since the volume of the surfactant-rich phase must be manageable, a compromise must be reached so that the surfactant concentration will allow a high phase ratio and a manageable surfactant-rich phase. The phases ratio is an important factor, which has an effect on the extraction recovery of cations.…”
Section: Sample Sizesmentioning
confidence: 99%
“…It is reported that the greatest analyte preconcentration factor is achieved when the CPE process is conducted with equilibration temperatures that are well above the cloud point temperature of the surfactant. 31 Increasing time and temperature is necessary for having complete reaction, facile separation and complete pre-concentration, therefore, by increasing them the absorbance will be increased. From the optimum points on, there is a probability for collapsing the formed complex and weak clouding of the surfactants, therefore, absorbance will be decreased.…”
Section: Effects Of Equilibration Temperature and Timementioning
confidence: 99%